2007
DOI: 10.1590/s0102-09352007000300017
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos maleato de timolol 0.5% do cloridrato de dorzolamida 2%, e da associação de ambas na pressão intra-ocular

Abstract: RESUMOAvaliaram-se efeitos da dorzolamida do timolol e da combinação de ambos sobre pressão intra-ocular (PIO) de cães normais, além de alterações no olho contralateral, não-tratado. Foram utilizados 60 cães sadios, distribuídos em três grupos (G) de 20 animais. No primeiro grupo (GT), foi avaliada a ação do maleato de timolol 0,5% na PIO; no segundo (GD), a ação do cloridrato de dorzolamida 2%; e, no terceiro (GTD), o efeito da associação fixa timolol/dorzolamida. A PIO foi aferida utilizando-se tonômetro de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
1
2
0
4
Order By: Relevance
“…Our results were similar to those described in a previous research conducted in healthy dogs, that also reported the efficaciousness of the combination of dorzolamide/timolol in reducing the IOP (BORGES et al, 2007). Notwithstanding, BORGES et al (2007) assessed the IOP-lowering effect of the fixed combination of dorzolamide/timolol after a single instillation, for only eight hours, and only considered to compare the effect of the treated eye with the control eye.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our results were similar to those described in a previous research conducted in healthy dogs, that also reported the efficaciousness of the combination of dorzolamide/timolol in reducing the IOP (BORGES et al, 2007). Notwithstanding, BORGES et al (2007) assessed the IOP-lowering effect of the fixed combination of dorzolamide/timolol after a single instillation, for only eight hours, and only considered to compare the effect of the treated eye with the control eye.…”
Section: Resultssupporting
confidence: 90%
“…When dorzolamide is used as a monotherapy, the drug significantly decreases IOP in healthy and glaucomatous dogs (CAWRSE et al, 2001;GELATT & MACKAY, 2001). However, the fixed combination of dorzolamide with timolol maleate, a nonselective beta blocker, proved to be more effective than dorzolamide alone, in reducing the IOP and pupil diameter (PD) in glaucomatous and healthy dogs (PLUMMER et al, 2006;BORGES et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Para estimativa dos efeitos adversos sob a superfície ocular realizou-se exame sistemático das pálpebras e suas margens, das conjuntivas, córnea e caracterização da secreção ocular com auxílio de oftalmoscópio direto 3 (Beta 200) com feixe de luz em fenda e filtro azul, diariamente. Além da avaliação oftalmológica diária, foi mensurada a espessura corneana central (ECC) com paquímetro ultra-sônico 4 no início e ao final do experimento.…”
Section: Protocolo De Avaliação Oftalmológicaunclassified
“…O glaucoma é uma neuropatia óptica progressiva multifatorial [4,26] que possui como principal fator de risco para o seu desenvolvimento o aumento da pressão intraocular (PIO) [6]. Reveste-se de singular importância por ser considerada a principal causa de cegueira irreversível em seres humanos e cães.…”
Section: Introductionunclassified
See 1 more Smart Citation